Association Between Subclinical Mastitis Markers and Body Condition Scores of Holstein Cows in the Black Sea Region, Turkey - Atasever, S.; Erdem, H. (Medwell Online, 2009)
This study was conducted to determine the relationships between subclinical mastitis and Body Condition Scores (BCS) in Holstein cows raised at the Black Sea region of Turkey. Somatic Cell Count (SCC) and Electrical Conductivity of milk (EC) levels were used as Subclinical Mastitis Markers (SMM). With 28 days intervals, milk samples and scoring values were taken and assessed within 3 different stages of lactation and into 4 seasons. Statistical analyses were performed with MINITAB. It was determined that SMM increased at summer and autumn seasons, however BCS had a variable trend. There was no difference between SMM by stage of lactation, but value of BCS was higher in the first stage of lactation. When, SMM evaluated by 3 different BCS subgroups, there was no significant difference determined between selected SMM. In this study, it was not defined any correlation between SMM and BCS. As result, effective factors on milk quality and feeding programs should be reconsidered at hot or rainy seasons and later stages of lactation. © Medwell Journals, 2009.
Keywords: Body Condition Score; Electrical Conductivity of Milk; Holstein; Somatic Cell Count; Subclinical Mastitis